Theology, Mysticism, and the Transformation of Science and Knowledge in Islamic Civilization in the Abbasid Era - Rohmad, Alif; Fanani, Zainuddin (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
The Abbasid era marked the peak of scientific development in Islamic civilization, characterized by the integration of theology, mysticism, and philosophy. This journal analyzes the close relationship between scientific rationality and religious spirituality, which gave rise to a new intellectual tradition that combined Greek thought with Islamic values. Philosophers such as Al-Kindi, Al-Farabi, and Ibn Sina contributed to aligning Greek philosophy with Islamic teachings, while theologians and Sufis like Al-Ghazali emphasized the importance of the spiritual dimension in science. This article discusses how the synthesis between rationalism and mysticism in the Abbasid era not only expanded the horizons of theological and philosophical thought but also influenced the development of science within a theological context. The research finds that although there was tension between rationalism and mysticism, both played an integral role in facilitating the transformation of science during that period. By examining the impact of this duality on the development of science, the journal asserts that the Abbasid period was the culmination of Islamic scientific history, which had a significant impact on the intellectual world until the modern era.   Keywords: Theology, Mysticism, Philosophy, Science, Abbasids, Rationalism, Sufism, Transformation of Knowledge